2010
DOI: 10.1152/ajpendo.00597.2009
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of gonadotropin-releasing hormone-1 gene transcription by members of the purine-rich element-binding protein family

Abstract: Zhao S, Kelm RJ Jr, Fernald RD. Regulation of gonadotropinreleasing hormone-1 gene transcription by members of the purinerich element-binding protein family. Am J Physiol Endocrinol Metab 298: E524 -

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 88 publications
0
3
0
Order By: Relevance
“…One study seeking to identify novel DNA-binding proteins for gonadotropin-releasing hormone 1 ( GNRH1 ) promoter, identified both Purα and Purβ as potential regulators of GNRH1 gene expression. 38 Subsequent in vivo studies have confirmed binding of both Purα and Purβ to the upstream region of the GNRH1 gene. While overexpression of Purβ was shown to significantly downregulate GNRH1 expression in transiently transfected mouse GT1-7 cells, this could not be demonstrated for Purα.…”
Section: Discussionmentioning
confidence: 97%
“…One study seeking to identify novel DNA-binding proteins for gonadotropin-releasing hormone 1 ( GNRH1 ) promoter, identified both Purα and Purβ as potential regulators of GNRH1 gene expression. 38 Subsequent in vivo studies have confirmed binding of both Purα and Purβ to the upstream region of the GNRH1 gene. While overexpression of Purβ was shown to significantly downregulate GNRH1 expression in transiently transfected mouse GT1-7 cells, this could not be demonstrated for Purα.…”
Section: Discussionmentioning
confidence: 97%
“…cDNA was diluted two-fold in nuclease-free water for use in qRT-PCR. Primer sets for all genes were commercially synthesized (Invitrogen) and identical to those used previously for A. burtoni : CRF , CRF 1 , CRF 2 , CRF binding protein ( CRFbp ) [48] ; g3pdh , 18s rRNA [49] ; LHβ , FSHβ [29] , [50] ; and GnRH1 [51] , [52] . Each primer pair produced a single melting curve peak in the presence of cDNA template, and showed no or late amplification when water was used as a template in the reaction mix.…”
Section: Methodsmentioning
confidence: 99%
“…DUSP1 has also been observed in luteinizing hormone beta (LHb) subunit gene expression in gonadotrophs (Purwana, Kanasaki, Oride, & Miyazaki, 2010). A few studies in the mouse neuronal GT1-7 cells suggest that enhanced occupancy of GnRH 1 gene upstream promoter by a transcription factor purine-rich element-binding protein (PURA) downregulated GnRH 1 mRNA levels, suggesting PURA as a repressor of GnRH1 gene transcription (Zhao, Kelm Jr., Fernald, 2010). We note that migratory juncos showed higher level of PURA protein than residents, which could be related to delay in their reproduction.…”
Section: Endocrine Signaling Associated With Earlier Timing Of Reproduction In Resident Juncos-mentioning
confidence: 99%